Respuesta :

Answer:

Option B

Step-by-step explanation:

By the midsegment theorem,

"Midsegment of a trapezoid is half the sum of the parallel bases"

By this theorem,

y + 6 = [tex]\frac{1}{2}[(3y-7)+(y+3)][/tex]

2(y + 6) = (3y + y) +(-7 + 3)

2y + 12 = 4y - 4

2y - 4y = -12 - 4

-2y = -16

2y = 16

y = 8

Therefore, length of the midsegment = y + 6

                                                              = 8 + 6

                                                              = 14

Option B will be the answer.

ACCESS MORE